2012
DOI: 10.1097/aud.0b013e3182498c28
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological Properties of Cochlear Implantation in the Gerbil Using a Flexible Array

Abstract: Objectives Cochlear implants (CI) perform especially well if residual acoustic hearing is retained and combined with the CI in the same ear (also termed hybrid or electric-acoustic stimulation). However, in most CI patients, residual hearing is at least partially compromised during surgery, and in some it is lost completely. At present, clinicians have no feedback on the functional status of the cochlea during electrode insertion. Development of an intraoperative physiological recording algorithm during electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
45
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 28 publications
(39 reference statements)
2
45
0
Order By: Relevance
“…Gross intracochlear trauma (e.g. rupture of the basilar membrane) should cause an immediate reduction or loss of the ECoG signal Ahmad et al, 2012;Campbell et al, 2010;Choudhury et al, 2011Choudhury et al, , 2014DeMason et al, 2012]. In our series, the largest decrease in the ECoG signal was 4.9 dB at 500 Hz.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Gross intracochlear trauma (e.g. rupture of the basilar membrane) should cause an immediate reduction or loss of the ECoG signal Ahmad et al, 2012;Campbell et al, 2010;Choudhury et al, 2011Choudhury et al, , 2014DeMason et al, 2012]. In our series, the largest decrease in the ECoG signal was 4.9 dB at 500 Hz.…”
Section: Discussionmentioning
confidence: 74%
“…We monitored the ongoing ECoG signal at suprathreshold intensities as a decrease in this signal has been the most sensitive marker for cochlear trauma in animal studies Ahmad et al, 2012;Campbell et al, 2010;Choudhury et al, 2011Choudhury et al, , 2014DeMason et al, 2012]. Gross intracochlear trauma (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that a decrease of the ongoing ECoG at low frequencies is a reliable marker for intracochlear trauma during insertion of an electrode (19)(20)(21)(22)(23)(24)37). In cochlear implant recipients, findings thus far have suggested that a decrease of low-frequency ECoG signals at suprathreshold intensities during surgery results in hearing loss of >10 dB or complete hearing loss in a majority of patients (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Electrocochleography (ECoG) has shown great potential in this regard and has been conducted in animal studies (19)(20)(21)(22)(23)(24) as well as during and after cochlear implantation in humans (9)(10)(11)(25)(26)(27)(28)(29). To our knowledge, four reports have correlated intraoperative ECoG findings with postoperative hearing preservation rates (9)(10)(11)28).…”
mentioning
confidence: 99%
“…However, reversible damage was not observed. Insertions with a flexible electrode mimicking a clinic implant have been done in normal-hearing animals 17 . In that condition, the responses to different frequencies showed complex changes as the electrode longitudinally traversed the basal turn.…”
Section: Introductionmentioning
confidence: 99%